2022
DOI: 10.7759/cureus.30355
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Patellofemoral Pain and Knee Pain in the General Population of Saudi Arabia

Abstract: BackgroundPatellofemoral pain (PFP) is a common cause of knee pain. This condition can restrict daily activities by trying to avoid activities that aggravate their pain. This study aimed to determine the prevalence of PFP and knee pain and its associated factors among Saudi young adults. MethodsA descriptive cross-sectional study was conducted in Saudi Arabia. A validated translated Arabic questionnaire was used. Data was collected through an online self-administered questionnaire. Saudi young adults of both g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
3
1
Order By: Relevance
“…In men, the prevalence of PFP was 42.2%, whereas in women, it was 42.6%. When contrasted to the findings of the study by Aldharman et al (15) , which indicated a total prevalence of 30.3%, a prevalence of 31.4% within men, and a prevalence of 29.5% within females, the present prevalence is greater. We observed a greater prevalence in general in our study compared to the one reported by Xu et al, where the general prevalence was 20.7%, PFP prevalence within males was 20.3%, while PFP prevalence within females was 21.2% (14).…”
Section: -Patellofemoral Pain Prevalence and Gender Associationcontrasting
confidence: 96%
See 3 more Smart Citations
“…In men, the prevalence of PFP was 42.2%, whereas in women, it was 42.6%. When contrasted to the findings of the study by Aldharman et al (15) , which indicated a total prevalence of 30.3%, a prevalence of 31.4% within men, and a prevalence of 29.5% within females, the present prevalence is greater. We observed a greater prevalence in general in our study compared to the one reported by Xu et al, where the general prevalence was 20.7%, PFP prevalence within males was 20.3%, while PFP prevalence within females was 21.2% (14).…”
Section: -Patellofemoral Pain Prevalence and Gender Associationcontrasting
confidence: 96%
“…Among those who have been through a divorce, 26.7% reported knee pain, while 16.7% of those who have been widowed reported the same. This is identical to the findings of the Aldharman et al study, which indicated that marital status, age 18-25, and age 26-35 were the best predictors of a greater PFP rate (15) . The study by Cook et al, which examined the relationship between PFP and variables like age, gender, and marital status, came to a different conclusion (23) .…”
Section: -Marital State Associationsupporting
confidence: 89%
See 2 more Smart Citations
“…Patellofemoral pain and instability are common causes of anterior knee pain and disability in adults and children alike [ 2 , 14 , 18 ]. The prevalence of patellofemoral pain is 22.7% and 28.9% in adults and adolescents, respectively [ 16 ], and the incidence of patellar instability has been reported to be as high as 29 per 100,000 adolescents [ 5 ].…”
Section: Introductionmentioning
confidence: 99%